English and mother-tongue-based multilingual education: Language attitudes in the Philippines - Mahboob, Ahmar (Archīum Ateneo, 2013)
In this paper, we will problematize the proposed use of mother-tongue-based instruction in the Philippines. As a country that has, for almost a century, supported the use of English in schools, this proposal marks a drastic shif in Philippine languages in education policies. We argue that a century of language policies, which have privileged English over all the local languages of the Philippines, have led to specifc attitudes to language that will impact on the success of mother-tongue-based education. To support our arguments, we will draw on the results of a survey on language attitudes conducted in the Philippines. Tis survey specifcally asked respondents about what they perceived to be the role/s of English and other Philippine languages in education. We argue that although mother-tongue initiatives are admirable, they need to be examined in terms of attitudes to language, which may or may not value mother tongues. In addition, we argue that for mother-tongue-based education to succeed, it is necessary to consider the possibility of changing these attitudes to language via a principles-based approach to language policy.